The “Canone Inverso”: when tobacco was not so bad. A Look Back at the Primordial Debate on the tobacco effects in the Occupational Medicine - Marinozzi, Silvia; Iorio, Silvia; Licata, Marta; Gulino, Matteo (Acta Biomedica Atenei Parmensis, 2018)
Aim: The article provides an overview on the beginning and evolutions of medical observations on tobacco induced diseases between Eighteenth and Nineteenth century. Methods: By searching for historical medical literature, first studies on tobacco-induced diseases focused on production risks rather than on adverse effects that the use of tobacco has for the human health. Results: The approach induced first eighteenth-century authors to define this substance as a non-pathogenic and, consequently, not to consider tobacco factories dangerous for health workers. In those years, tobacco was employed in therapy as a stimulant treatment and it was considered harmless and even healthy and preventive of several acute diseases. Conclusions: Authors will show that studies on pathogenic effects of smoking will only start around late nineteenth century, when the idea of the healthiness of tobacco industry was already supported.